Optimal surgical margin for penile‐sparing surgery in management of penile cancer—Is 2 cm really necessary?. Issue 4 (5th February 2021) - Anderson, Elliot; Yao, Henry Han‐I; Chee, Justin
Abstract: Introduction: Classical teaching of a 2 cm macroscopic surgical margin for surgical treatment of primary penile cancer is overly aggressive. Contemporary evidence suggests narrow but clear margins have similar survival outcomes for localized disease. This study aims to determine the oncological outcome of using a risk‐adapted algorithm to selection of macroscopic surgical margin based on biopsy grade of disease: 5 mm margin for grade 1, 10 mm margin for grade 2, and 20 mm margin for grade 3. Methods: This is a retrospective case series of patients who underwent penile‐sparing surgery for biopsy‐proven penile SCC by a single surgeon from May 2010 through to January 2019. Clinicopathological data were extracted from medical records. Primary outcome was the positive margin rate. Secondary outcomes were overall survival (OS), cancer‐specific survival (CSS), metastasis‐free survival (MFS), and local recurrence‐free survival (RFS). Kaplan‐Meier survival analysis was used to determine survival outcomes. Results: A total of 21 patients were included in this study. The median age was 65. Pre‐operative biopsy grade was grade 1 in 19.1% of patients, grade 2 in 47.6%, and grade 3 in 33.3%. The median size of tumor on examination was 20 mm. Using a grade‐stratified algorithm for macroscopic surgical margin, only one patient (4.8%) had a positive margin. This patient had G1T3 disease and proceeded to have a total penectomy for oncological clearance. The median margin clearance was 7 mm. The 12‐month OS, CSS, MFS, and local RFS were 94.6%, 94.6%, 81.0%, and 92.3%, respectively. Conclusion: This study suggests that using a grade‐stratified approach to aim for a narrower macroscopic surgical margin does not appear to significantly alter the oncological outcome, with a negative margin rate of 95.2% in our this series. This enables more men to be eligible for organ preserving surgery and thereby improve their quality of life in the urinary function and sexual function domain. Larger prospective studies are warranted to confirm these findings.